Magneto Hydrodynamic and Bio-Convection Effects on Hybrid Nanofluid Dynamics Over an Inverted Rotating Cone with Different Base Fluids - Balaji Padhy; Archana Senapati; Goutam Kumar Mahato; P.K. Rath (East European Journal of Physics, 2024)
This study explores the combined effects of magnetohydrodynamics (MHD) and bio-convection on the flow dynamics of hybrid Nanofluids over an inverted rotating cone with different base fluids. The hybrid Nanofluids, composed of nanoparticles suspended in various base fluids, exhibit unique thermal and flow characteristics due to the interplay between magnetic fields and bio-convection phenomena. The governing equations, incorporating the principles of MHD and bio-convection, are derived and solved using numerical methods. The analysis considers the impact of key parameters such as magnetic field strength, the rotation rate of the cone, nanoparticle volume fraction, and types of base fluids on the flow behaviour, heat transfer, and system stability. Results indicate that the MHD significantly influences the velocity and temperature profiles of the hybrid Nanofluids, while bio-convection contributes to enhanced mixing and heat transfer rates. Additionally, the choice of base fluid plays a critical role in determining the overall performance of the hybrid Nano fluid system. This study provides valuable insights into optimizing the design and operation of systems utilizing hybrid Nanofluids in applications where MHD and bio-convection effects are prominent.